Analisa Penyelesaian Kredit Macet Yang Telah Hapus Buku (Studi Kasus di Sentra Kredit Kecil Serang PT BNI, Tbk) - , Ansar Faisal ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study was to assess the policies taken in the settlement of write-off credit using Net Present Value method. The data used consist of write-off credit data on Sentra Kredit Kecil Serang from 2004 through 2011, the data used is an write-off credit of debtor data with a maximum of Rp. 1 billion or over who are not related to legal issues. Net Present Value analysis done by estimating the nominal and the time of redemption if credit facilities is paid through the auction method, there for KPKNL or Private Auction Hall. Nominal obtained is present valued then compared with the amount of the completion done by the debtor. If the nominal settlement is greater, then the repayment of the discount can be given, and if not then the discount can not be given. From the research results using the Net Present Value method, obtained the value of repayment for borrowers who had repaid the loan is greater than the present value of repayment if the Bank done through an auction.